The changing role and definitions of aquaculture for environmental purposes - Darien D. Mizuta; Halley E. Froehlich (John Wiley & Sons Australia, Ltd, 2025)
Aquaculture is the fastest growing form of food production across the globe. The expansion of the industry has brought about a diversity of approaches to mitigate social and ecological impacts associated with aquaculture production systems. At the same time, there is a growing interest in utilizing aquaculture for conservation purposes including species recovery, habitat restoration and offsetting the impacts of wild capture on vulnerable harvested species. The diversification of the aquaculture sector and the overlapping use of terminology to describe alternative aquaculture approaches can create challenges for policy makers, managers and industry practitioners. Clear distinction between alternative aquaculture approaches and intent may improve regulatory, permitting, monitoring and consumer awareness outcomes. Here, we examine the use of four primary aquaculture approaches in the scientific literature: ‘commercial aquaculture’, ‘conservation aquaculture’, ‘restorative aquaculture’ and ‘regenerative aquaculture’ to elucidate the similarities and differences and improve understanding of the approaches. We propose definitions for the terms based on empirical analysis of related words used in scientific texts and fitness into a particular initiative. In addition, we discuss the use of those terms within the context of benefits to ‘people and nature’, namely activities that include economic, social and environmental outcomes and the variability therein. Clear definition of terms and related activities in a burgeoning field can minimize semantic confusion while improving opportunities to craft robust policy guidelines and improve stakeholder understanding and practice of aquaculture activities.